Alloying effects on properties of Al2O3 and TiO2 in connection with oxidation resistance of TiAl. (January 2016) - Ping, Fa-Ping; Hu, Qing-Miao; Bakulin, Alexander V.; Kulkova, Svetlana E.; Yang, R.
Abstract: In the present work, a first-principles method is used to calculate the oxidation energies of Al2 O3 and TiO2 as well as the formation energy of oxygen vacancy in TiO2 containing various alloying elements, in order to shed some light on the alloying effects on the oxidation resistance of γ -TiAl. Our calculations demonstrate that almost all alloying elements increase the oxidation energies of Al2 O3 and TiO2 . The alloying elements with number of d electrons from 2 to 5 in the forth and fifth rows of the periodic table (e.g., Zr, Nb, Mo, Hf, Ta, W) increase significantly the oxidation energy difference between Al2 O3 and TiO2, i.e., reduce the relative stability of Al2 O3 to TiO2 . On the other hand, these alloying elements increase the formation energy of oxygen vacancy in TiO2 . The effects of other alloying elements are less significant or opposite. Observing the experimental mass gains of TiAl alloys and unalloyed TiAl due to oxidation, we find that the elements reducing the relative stability of Al2 O3 to TiO2 and increasing the formation energy of oxygen vacancy enhance the oxidation resistance of TiAl whereas others do not. Such correlations are rationalized by analyzing the alloying effects on the internal oxidation of Al in the γ -TiAl matrix and the diffusion of oxygen in TiO2 surface scale. Highlights: The alloying elements such as Zr, Nb, Mo, Hf, Ta, W reduce the relative stability of Al2 O3 to TiO2 . The alloying elements such as Zr, Nb, Mo, Hf, Ta, W increase the formation energy of oxygen vacancy in TiO2 . The relative stability and vacancy formation energy correlate well to the oxidation resistance of γ-TiAl based alloys.